1990
DOI: 10.1002/polb.1990.090281103
|View full text |Cite
|
Sign up to set email alerts
|

Gel permeation chromatograph interface to collect solvent‐free polymer fractions for composition drift analysis

Abstract: An interface is described that is capable of stripping solvent from polymer solutions emerging from an interfaced high‐temperature gel permeation chromatograph. The chemical composition of each solvent‐free polymer fraction is then determined using Fourier transform infrared (FTIR) or other techniques to obtain the composition drift (CD) pattern of the polymer (i.e., variation of chemical composition as a function of molecular weight). The interface consists of a vacuum oven into which an ultrasonic nebulizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…' This reduction likely results from there being six data points instead of seven as in all other photoenlargements of published plots in Ref. 10.…”
Section: Linearization Of Log 7 Versus T / Tg Plotsmentioning
confidence: 86%
See 2 more Smart Citations
“…' This reduction likely results from there being six data points instead of seven as in all other photoenlargements of published plots in Ref. 10.…”
Section: Linearization Of Log 7 Versus T / Tg Plotsmentioning
confidence: 86%
“…Visual inspection of Figure 2 in Ref. 10 and of our extrapolated generic line in Figure 1 suggested that T/Tg reaches an asymptotic limit (T/T,), at about 1.21 and a log 5, of -6 or longer. I t also appeared likely from their Figure 2 that individual polymers would exhibit (T/Tg), values at an associated log rc that was polymer specific, depending on flexibility of the chain.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Several types have been used including ultrasonics [95,121]; monodisperse aerosol generators (MAGIC) [92,[96][97][98][99][100][101]; and ones for gradients, which can be programmed to change temperature as the mobile phase changes [74,102]. Several types have been used including ultrasonics [95,121]; monodisperse aerosol generators (MAGIC) [92,[96][97][98][99][100][101]; and ones for gradients, which can be programmed to change temperature as the mobile phase changes [74,102].…”
Section: General Description and Interfacesmentioning
confidence: 99%
“…Aluminium foil was placed on the underside of the disk, allowing double absorption through reflection of the IR beam. Further improvements were made to the nebulization of the aerosol 10,11 and later a commercial company started manufacturing and selling analytical instruments that operate on this concept. 12 In the years following the major contributions to epoxidized natural rubber (ENR) research, not much emphasis was placed on the analysis of these samples.…”
Section: Introductionmentioning
confidence: 99%